The Exoplanet Revolution - Lequeux, James (Current Natural Sciences, 2020)
More than 4300 planets around nearby stars! Who could have imagined this extraordinary harvest only thirty years ago? As the vast majority of stars are surrounded by planets, we can surmise that there must be more than a hundred billion planets in our Galaxy. The Solar system is therefore very far from unique. However, it looks quite different from most of the external systems that we know today, but the variety of planetary systems is such that it is difficult to conclude that the Solar System is truly particular. Understanding how diverse planet systems were formed and how they evolved, studying the nature of exoplanets and their atmospheres, are challenges that hundreds of researchers around the world are working on. Does any of these planets harbor life? We do not yet have an answer, but the new means of observation and analysis that astronomers have and will soon have at their disposal are so powerful that they could give a first answer in a few decades, and perhaps even in a few years if we are lucky. This book gives a comprehensive vision of this complex and fascinating area of research, presented in a simple and lively way.